Republic of Tunisia - Yew, Meng Lai; Ayub, Zainal Amin; Ahmad, Abdul Razaq; Chang, Da Wan; Ismail, Russayani (Springer, 2016)
The Republic of Tunisia makes an interesting case study in the context of higher education development in the MENA region.This is in view of its strong tradition and culture of promoting education, and the accolade it receives for possessing among the most developed higher education systems in the region, despite its comparatively less affluent economic condition. This chapter examines the development of the national higher education agenda of Tunisia, in terms of the provision of international students, research, and training collaboration, as well as network expansion.It explores the challenges and prospects offered from the politico-security, economic, social, legal, and educational perspectives as a means to develop important insights that could assist in the making of strategic recommendations for would-be higher education providers and their higher education institutes, in the quest to extend their outreach to this post-conflict state in the MENA region.